SATISFACTION WITH FAMILY ENVIRONMENT: THE ADAPTATION OF IDEAL FORM OF FAMILY ENVIRONMENT SCALE IN THE CULTURAL ENVIRONMENT OF LATVIA - Dombrovskis, Aivis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In the article “Satisfaction with Family Environment: The adaptation of Ideal form of Family Environment Scale in The cultural environment of Latvia”, author presents results and way of adaptation of Family Environment Scale – I form (FES-I) in cultural environment of Latvia, because this tool wasn’t adapted. Representative sample of research consisted from 501 respondents in age from 18 to 27 (M = 20,33; SD= 1,94). At the same time author shows how to determine satisfaction with family environment using the Satisfaction with Family Environment – Real form and FES – I form. There are used methods of statistic which are recommended for processes of tests’ adaptation, namely, Cronbach’s alpha, factorial, divergent and convergent validity, linguistic validity. The main goal was to provide a qualitative process of FES- I adaptation in cultural environment of Latvia, to provide a qualitative tool for specialists to research family environment. During the research the main psychometric indicators of the tests were calculated and the tool was successfully adapted in cultural environment of Latvia.